Teacher in Scientific Research by Bishop Zygfryd Ignacy Kowalski (1910-1995) - Władysława Szulakiewicz (Multidisciplinary Journal of School Education)
Research aims and problems: The aim of this article is to present the pedeutological views of Bishop Zygfryd Ignacy Kowalski, who lived from 1910 to 1995. He studied pedagogy at Nicolaus Copernicus University in Toruń (UMK). Alongside his pastoral duties, he worked as a religion teacher in schools in Toruń, including at the Pedagogium, and later lectured in pedagogy and didactics at the Seminary for Priests in Pelplin. The main focus of this paper is Fr. Kowalski’s pedeutological thought. The article seeks to answer specific questions concerning: his pedagogical studies as a preparation for his pedagogical studies, his research on teachers in both published and unpublished works, and his research methods.